The Debiasing of Forecasts in Research and Development - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 1971)
A possible way to improve the accuracy of forecasts is to estimate (and subsequently remove) any systematic bias by reference to the bias found in similar forecasts in the past. This paper discusses the applicability to industrial R & D of a method proposed by Summers for debiasing estimates of the costs of military projects by means of a regression equation derived from past experience, and gives the results of applying a similar method to estimates of costs, sales, product prices, and return factors for ten industrial development projects.